Предварительные результаты исследования кургана скифского времени у хут. Березовка - Лысенко, С.Д. (Археологічні дослідження в Україні, 2009)
In May—June, 2008, Fastiv archaeological expedition conducted protective excavations of the mound on the site of construction of the housing estate «Olimpic Park» near Berezivka hamlet in Makariv Region of Kyiv Oblast. The vault of the 4th c. BC has been studied.